JOB COSTING: EMPIRICAL EVIDENCE OF BAKERY PRODUCTION - Ali Jalal Awqati (LPPM Univ Potensi Utama, 2020)
In the use of job cost data from Erbil's leading bakery store, this research empirically examines item price conduct both before and after a shift in the costing scheme for work orders. Since direct material expenses are charged individually and labor costs are fixed, this business varies only by a minimal percentage of the labor costs. The main finding is that assigned fixed work expenses, even after monitoring for work quantity and quality specifications, are important in explaining differences in short-term prices. The findings also demonstrate that pricing conduct has altered as a result of the work costing system change. After the change, prices are more dependent on the full cost calculated based on the system, although marketing managers were not informed of any cost estimates when bidding for jobs.